2013
DOI: 10.1089/ten.tea.2012.0497
|View full text |Cite
|
Sign up to set email alerts
|

Composite Growth Factor Supplementation Strategies to Enhance Tenocyte Bioactivity in Aligned Collagen-GAG Scaffolds

Abstract: Biomolecular environments encountered in vivo are complex and dynamic, with combinations of biomolecules presented in both freely diffusible (liquid-phase) and sequestered (bound to the extracellular matrix) states. Strategies for integrating multiple biomolecular signals into a biomimetic scaffold provide a platform to simultaneously control multiple cell activities, such as motility, proliferation, phenotype, and regenerative potential. Here we describe an investigation elucidating the influence of the dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 64 publications
9
103
0
Order By: Relevance
“…When studied in small animal models of tendon healing, however, results were varied [29][30][31] . In this study, treatment of tenocytes with PDGF reduced the expression of the major tenocyte genes, scleraxis and tenomodullin, and previous studies also demonstrated that PDGF may have a detrimental effect on tendon gene expression 19 . Clinically, PDGF receptor expression is increased in diseased tendons, and is associated with hypercellularity 32 , and taken into context with our findings on the poor effects of PDGF on tendon-related genes, this suggests that PDGF may not be the most suitable factor for improving tendon healing outcomes.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…When studied in small animal models of tendon healing, however, results were varied [29][30][31] . In this study, treatment of tenocytes with PDGF reduced the expression of the major tenocyte genes, scleraxis and tenomodullin, and previous studies also demonstrated that PDGF may have a detrimental effect on tendon gene expression 19 . Clinically, PDGF receptor expression is increased in diseased tendons, and is associated with hypercellularity 32 , and taken into context with our findings on the poor effects of PDGF on tendon-related genes, this suggests that PDGF may not be the most suitable factor for improving tendon healing outcomes.…”
Section: Discussionsupporting
confidence: 74%
“…The use of growth factors for treating tendon disorders has failed to have a clinical impact. PDGF is one of the most widely studied factors for improving tendon healing, and in vitro results have been especially positive, with potent increases in tendon cell and explant proliferation and collagen production observed 19,20,26 . When studied in small animal models of tendon healing, however, results were varied [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advancements in engineering, chemistry and biology have made available numerous technologies that allow fabrication of hierarchical threedimensional scaffolds that closely imitate native tendon architectural features and mechanical properties, whilst enabling localised and sustained delivery of therapeutics [350]. Collagen sponges, for example, with or without aligned tracks and loaded with GAGs, growth factors and various cell populations have demonstrated enhanced cell motility and phenotype maintenance in vitro and increased collagen expression levels in small animal models [351][352][353][354][355]. However, such scaffold conformations cannot provide adequate mechanical resistance, in such a high mechanical demand environment [356].…”
Section: Bottom-up Approached For Tendon Repair Based On Natural In Omentioning
confidence: 99%